Pengendalian Nematoda Puru Akar (Meloidogyne spp.) pada Buncis dengan Bakteri Pasteuria penetrans dan Solarisasi - B. Triman; Mulyadi Mulyadi (Universitas Gadjah Mada, 2001)
The objectives of the research were to study the effect of P. penetrans and soil solarization on the population of root-knot nematodes (Meloidogyne spp.) and the effect of soil solarization on the infectivity of P. penetrans. The research was done in the field with high population of plant parasitic nematode especially root-knot nematodes. Soil solarization was done in dry season by covering the soil before french beans (buncis) were planted with transparent plastic and P. penetrans were inoculated before soil solarization. Factorial design in Completely Randomized Design was used in this experiment with the following factors: 1) soil solarization (within 1, 2, and 3 moths); 2) isolates of P. penetrans (i.e. isolate 2 and 3). The research results were: 1) Isolate 2 and 3 of P. penetrans were able to parasitize root-knot nematodes in soil solarized within 1, 2, and 3 months; 2) the length of soil solarization afected the infectivity of P. penetrans on Meloidogyne spp. The percentages of Meloidogyne spp. infected with isolate 2 of P. penetrans in soil solarization within 1, 2, and 3 months were 40.3%; 25.7%, and 10.1%, respectively, whereas in soil inoculated with isolate 3 of P. penetrans were: 37.3%, 10.2%, and 2.2%, respectively; 3) inoculation of P. penetrans reduced the root damage caused by root-knot nematodes (Meloidogyne spp.); and 4) treatment of P. penetrans combined with soil solarization reduced the root damage caused by root-knot nematodes (Meloidogyne spp.).